Analisis Pelaksanaan Prinsip Transparansi APBNag Cubadak di Kabupaten Tanah Datar tahun 2020-2022. - Adinda Charisma Nafisa; Bagas Islam Mahendra; Diffa Khoirunnisa; M .Afif Wardana; Salsa Auliamri Putri; Irawati Irawati; Mhd Fajri (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2024)
Abstract Good governance has now become a standard or paradigm that needs to be applied in governance because good governance is based on principles such as participation, transparency, accountability and efficiency. One of the principles of good governance is transparency, where transparency can be interpreted as an openness of government in managing public resources. Nagari Revenue and Expenditure Budget (APBNag) is a village regulation that makes sources of revenue and allocation of village expenditure within one year. Nagari Cubadak is one of the villages that has a good reputation or report card in terms of transparency in managing the APBNag. This is then the background of this research. This study aims to analyze the implementation of the principle of transparency of the Cubadak APBNag in Tanah Datar Regency for 2020-2022. The approach in this study uses a qualitative approach with data collection techniques using interview and observation methods. The types of data used are primary data and secondary data. Based on the results of the study, the researcher draws the conclusion that the Cubadak Nagari Government has carried out consistent transparency of APBNag management for the last 3 years well. The application of the principle of transparency is also in accordance with the indicators of transparency according to Krina, namely the provision of clear information, easy access to information, establishing a complaint mechanism, and increasing the flow of information through cooperation with the mass media and non-governmental organizations. Keywords: Good governance; Transparency; APBNag